All Days 1995
DOI: 10.2118/30483-ms
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Fracture Geometry in the Naturally Fractured Antrim Shale

Abstract: The Antrim Shale of the Michigan Basin has been an active gas play with over 3,500 wells drilled over the last 5 years. There is substantial evidence that the Antrim must be fracture stimulated to be economical and that two~stage treatments provide the best results. However, due to the shallow depths (500-2300 ft) and naturally fractured nature of the Antrim, fracture geometry is complex, and determination of optimal fracture treatments is not straight forward. Because historical field comparisons did not prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Although Figure 1(a) is more accurate in its scaling and depiction of a cross-section of the geologic strata, it is true that not all gas wells occur this deep. For example, coal bed methane wells and parts of Michigan's Antrim shale are atypically shallow, with production occurring at depths of less than 1,000 feet below the surface (Hopkins et al 1995;Jenkins and Boyer 2008).…”
Section: Fracture Network and Groundwater Contaminationmentioning
confidence: 99%
“…Although Figure 1(a) is more accurate in its scaling and depiction of a cross-section of the geologic strata, it is true that not all gas wells occur this deep. For example, coal bed methane wells and parts of Michigan's Antrim shale are atypically shallow, with production occurring at depths of less than 1,000 feet below the surface (Hopkins et al 1995;Jenkins and Boyer 2008).…”
Section: Fracture Network and Groundwater Contaminationmentioning
confidence: 99%
“…One possible explanation for this is that the hydraulic fracture propagates at an angle to the wellbore following existing natural fractures, but connects to the hydraulic fracture in adjacent intervals through the natural/hydraulic fracture network. 20 The spinner surveys on the SDWs were helpful in confirming the overall gas production rate from the Lewis. However, due to tool resolution combined with the relatively low flow rates, the flow data from the individual layers within the Lewis was usually not diagnostic.…”
Section: Post-stimulation Testingmentioning
confidence: 99%
“…Studies of open-and cased-holed data have shown the possibility of multiple fractures which possibly propagate horizontally or nonvertically, intersecting the wellbore parallel or with natural fractures. 4 The goal of performing an injection analysis real-time is not to ascertain the exact fracture geometry but to recognize the symptoms and be adequately equipped to counteract. Fig.…”
Section: Stabilized Injection Periodmentioning
confidence: 99%